Comparison of MR-PWI quantitative and semi-quantitative parameters for the evaluation of liver fibrosis - Ke Ding; Manrong Liu; Xue Wei; Ruisui Huang; Jiong Chen; Shanjin Lu; Dacheng Wang; Wei Lu (BMC Medical Imaging, 2021)
Abstract Background To evaluate different stages of liver fibrosis in cynomolgus monkeys by comparing magnetic resonance-perfusion weighted imaging (MR-PWI) quantitative and semi-quantitative parameters, and confirm the best detection indicators for diagnosis of liver fibrosis. Methods A liver fibrosis model of different stages (S0–S4) was established in cynomolgus monkeys. The changes in MR-PWI quantitative and semi-quantitative parameters with the progression of liver fibrosis were investigated. Results MR-PWI quantitative parameters gradually decreased with the progression of liver fibrosis. Hepatic arterial perfusion index (HPI) was found to increase with the progression of liver fibrosis and significant differences of HPI between each group were observed. There was a highly positive correlation between HPI and the stages of liver fibrosis. Receiver operating characteristic (ROC) curve analysis showed that HPI had the highest efficacy of the MR-PWI quantitative parameters for the diagnosis of liver fibrosis. The MR-PW semi-quantitative parameters gradually reduced with the progression of liver fibrosis, and the differences were statistically significant between stages S3–S4 and S0–S2. Time to peak (TPP) gradually extended and showed a positive correlation with the stages of liver fibrosis. TTP had the highest efficacy of the semi-quantitative parameters for diagnosis of liver fibrosis. Conclusions Both the MR-PWI quantitative and semi-quantitative parameters of the liver fibrosis model in cynomolgus monkeys varied at different stages of liver fibrosis, and HPI and TTP were the best detection indices for quantitative and semi-quantitative evaluation of liver fibrosis, respectively.